Clinical and serological features of severe vasculitis in rheumatoid arthritis: prognostic implications. Issue 10 (October 1987) - Geirsson, A J; Sturfelt, G; Truedsson, L
Abstract : Sixteen patients with classic rheumatoid arthritis (RA) complicated by severe vasculitis were studied and compared with a matched control group of 16 RA patients without vasculitis. Seven of the patients with vasculitis died within 4 to 120 months (median 32 months) after developing vasculitic symptoms. Gangrene of digits and extremities, bowel ulcers or bowel perforation, or both, and cardiac involvement were more common among the patients who died than among those with a more favourable course. The present data suggest that large vessel vasculitis in RA is associated with high frequency of arteriosclerotic vascular disease. The serum concentrations of complement components C3 and C4 were lower, and concentrations of IgM rheumatoid factor, complement activating rheumatoid factor, and C1q binding immune complexes (C1q solid and C1q fluid phase assay) were significantly higher among vasculitic patients than in the control group. Laboratory data provided little prognostic information with regard to rheumatoid vasculitis, with the exception that IgM and IgG rheumatoid factors were significantly higher among patients with fatal course of disease than in those who achieved remission.